PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI PADA MATERI KERAGAMAN BUDAYA BERBASIS KEARIFAN LOKAL UNTUK SISWA KELAS IV SD NEGERI SIDOSARI: Penelitian Pengembangan - Eviyanti; Titi Anjarini; Suyoto (STKIP Subang, 2025)
Learning about the cultural diversity of local wisdom at Sidosari State Elementary School still experiences several obstacles. These obstacles are related to the lack of interesting and fun learning media to facilitate teachers and students. The purpose of this study was to produce and determine the feasibility of monopoly learning media on wisdom-based cultural diversity material based on validity, practicality, and effectiveness. The type of research method used is research and development (Research and Development) with the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 20 fourth grade students of Sidosari State Elementary School. Data collection techniques and instruments in this study used observation, interviews, questionnaires, and tests. The data analysis technique used is the analysis of validity, practicality, and effectiveness. The results of this study found that the validity of the product obtained an average score of 3.55 with a very valid category. The practicality of the product obtained an average score of 3.75 with a very practical category. The effectiveness of the product in the limited trial obtained an average score of 0.55 with a medium effective category, while in the broad trial obtained an average score of 0.39 with a medium effective category. The development of monopoly learning media is expected to provide benefits and be used as an additional reference source to increase knowledge.